Exploration of The Interplay Between Tourism, Global Warming And Health In Nigeria - Musediq Olufemi Lawal; Kenneth Young Irhue (Administrative Law and Governance Journal, 2021)
Abstract It is obvious that tourism development has not been given serious attention in Nigeria, still the likely implications of global warming on it cannot be ignored. It is in view of this that this paper is exploring ways by which the two phenomena have been affecting each other.  Using Nigeria as a case, the implications of this on the health of the populace was given attention in the study. The change in the nature of the climate was mentioned as inevitable, so also is the possibility of this influencing the graceful spread of diseases among the populace. In the process, negative manifestation of warmer climate like increasing the risk of heat-related illnesses and death besides the worsen conditions for air quality was noted. Probable increase in the frequency and strength of extreme events (such as floods, droughts, and storms) that threaten human safety and health were highlighted and discussed.  The paper brought to the fore, the inherent benefits of tourism when it takes a sustainable approach, which include simultaneous control of ravaging global warming.  In view of this, the paper made case for sustainable tourism and jettisoning of traditional ideas of tourism development for optimization of the benefits inherent therein. Keywords: Global Warming, Tourism, Ecotourism, Conservation, Greenhouse Effect